The intention of using Facebook by postgraduate students for knowledge sharing: An empirical study - Selvarajah U.; Ali N. (Inderscience Publishers, 2023)
This study aims to develop a conceptual model that explains the factors that influence the use of Facebook by postgraduate students in Malaysia for knowledge sharing. This study adopted quantitative approach using survey as the data collection method. The data were collected from 206 postgraduate students from the public and private universities in Malaysia. The data were tested using Partial Least Square (PLS). The findings indicate that social interaction ties, perceived enjoyment, and trust have a significant relationship with the behavioural intention of postgraduate students to share knowledge via Facebook while perceived similarities do not affect their behavioural intention to share knowledge via Facebook. The findings extend the scope of the theory and contribute to the body of knowledge for the scope of postgraduate students and existing literature regarding social media adoption, specifically in the Malaysian context. Finally, this study provides suggestions for research and practical implications. Copyright 2021 Inderscience Enterprises Ltd.